HISTORIOGRAPHY TENDENCIES SEEN THROUGH THE DOCTORATE THESES IN SCIENCES OF EDUCATION. RUDECOLOMBIA (1998 - 2007) - Acuña Rodríguez, Olga Yanet (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
This article intends to make a reflection on the topics and methodologies used in the Doctor theses development, carried out in the Sciences of Education Doctorate - RUDECOLOMBIA. It is important to recall that the Doctorate Formation program basis was the research project, “History of the Colombian University, 1774 – 1992”, which has been enriched with both research and doctor theses contribution. Thus the University, the study object, has been studied from various historiography trends, in which its role in the national and local context is highlighted. This has allowed to identify several trends such as institutional history, social history of education, elites and political power, socio-cultural history, school knowledge history, all of which have also allowed to identify new problems, new methodologies, new characters, new sources. In turn, they have allowed to identify new problems, new methodologies, new actors, and new sources that are opposed to the historicism.